Design and synthesis of C-α-D-mannopyranoside linked mesoporous silica nanoparticles - Nechooli, Hemanth K.; Ramtenki, Vilas; Kumar, Chepuri V. Suneel; Prasad, V. B. L.; Ramana, V. Chepuri (Journal of Chemical Sciences, 2025)
Mannose functionalized mesoporous silica nanoparticles (MSNs) offer a promising approach for developing more targeted, effective, and safer cancer therapies. For many of the applications, immobilization of carbohydrates like mannose onto MSNs is a crucial aspect, and in most cases, mannose moieties are connected through O-glycosidic linkages that are susceptible to acidic/enzymatic hydrolysis. To generate a stable mannose-functionalized MSN, we designed a novel C(14)-alpha-mannosylated tetradeca-1-yne. The key steps involved in the synthesis of C-mannosylated alkyne are C1-alkynylation of tri-O-acetyl-D-glucal with 1-trimethylsilyl-tetradec-1-yne, followed by stereoselective dihydroxylation and the isomerization of the internal triple bond to a terminal position. This mannose ligand was then immobilized onto azidopropyl-functionalized SBA-15 through the Cu(I)-catalyzed azide-alkyne click (CuAAC) reaction. Various physical techniques such as low-angle powder XRD, N-2 adsorption isotherms (BET), Fourier transform infrared (FTIR), high-resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy (FE-SEM), and thermogravimetric analysis (TGA) have been employed to characterize this C-mannosyl SBA-15 silica matrix. We evaluated the binding ability of C-mannosyl SBA-15 nanoparticles by using fluorescein-labelled Con-A as a target protein.
Keywords: C-mannoside; Click reaction; mannose specific proteins; Mesoporous silica nanoparticles; Zipper reaction